Influence of reference groups of brand connectivity of consumers - Vimaladhevi, N.; Thaiyalnayaki , M. (Salud, Ciencia y Tecnología - Serie de Conferencias, 2024)
Purpose: the main aim of the study is to find the influence of reference groups on the factors of brand connectivity Method: the study depends upon the primary data obtained through a well structures questionnaire. The researcher applied convenience sampling method to obtain 389 responses from all the 15 zones of Chennai city and applied confirmatory factor analysis, structural equation model, linear multiple regression analysis and one-way analysis of the variance. Findings: it is found that the primary reference group comprises family members with intimate connection and close friends with a dominating type whereas the secondary reference group consist of office colleagues, professionals in the office and superiors and subordinates Practical Implications: the present research is focusing on the predominant reference groups frequently influences the changing behaviour of consumers and their brand choice behaviour, the factors directly determine the existence of profound brand connectivity among the consumers and to know the empirical relationship between reference group influences on brand connectivity perception of consumers in the study area. Originality/Value: the study focus on measuring the impact of reference group of customers in consolidating the brand connectivity between customers and brands on the basis of emotional attachment and brand performance and satisfaction